Analisis Dampak Transisi dari PSAK 13 ke PSAK 240 terhadap Kebijakan Pengukuran Nilai Wajar Properti Investasi pada Perusahaan Publik di Indonesia - Arya Putra Maulana; Margaretha Yeniwati; Duwi Duwi; Dewa Ayu Dita Sri Ardani; Rinny Meidiyustiani (Universitas Katolik Widya Karya Malang, 2025)
This study discusses the transition from PSAK 13 to PSAK 240, which will come into effect in 2024, particularly in relation to the measurement of fair value of investment properties in Indonesian public companies. This change in standards aims to strengthen alignment with IFRS (IAS 40) and promote transparency and comparability of financial statements. Through a Systematic Literature Review (SLR) approach of publications from 2021 to 2024, this study found that the use of fair value methods can increase the relevance of financial information and attract investor interest, although it has the potential to cause volatility in financial statements. The results of the study show that the successful implementation of PSAK 240 is influenced by the quality of governance, the availability of market data, and the readiness of the company's information system. In addition, factors such as company size, leverage, and managerial ownership also influence the choice of valuation method. Thus, the transition to PSAK 240 is not only a technical change but also a strategic step to strengthen the credibility of the Indonesian capital market.